2019
DOI: 10.3390/antiox8090340
|View full text |Cite
|
Sign up to set email alerts
|

Increase of 4-Hydroxybenzoic, a Bioactive Phenolic Compound, after an Organic Intervention Diet

Abstract: Consumption of organic products is increasing yearly due to perceived health-promoting qualities. Several studies have shown higher amounts of phytochemicals such as polyphenols and carotenoids in foods produced by this type of agriculture than in conventional foods, but whether this increase has an impact on humans still needs to be assessed. A randomized, controlled and crossover study was carried out in nineteen healthy subjects aged 18–40 years, who all followed an organic and conventional healthy diet, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…However, these phenolic compounds are widely distributed in foods other than peanuts. The absence of significant differences between WP and PB interventions could be due to high standard deviations, which can hinder statistical treatment, as has been observed in previous studies [ 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 94%
“…However, these phenolic compounds are widely distributed in foods other than peanuts. The absence of significant differences between WP and PB interventions could be due to high standard deviations, which can hinder statistical treatment, as has been observed in previous studies [ 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 94%
“…These results are in agreement with Zamora-Ros et al, who detected phenolic acids as the most abundant urinary MPM in adult participants in the European Prospective Investigation into Cancer and Nutrition (EPIC) study [ 31 ]. Similarly, Hurtado-Barroso et al found phenylacetic acids to be among the most abundant urinary MPM in young adults [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The production of this molecule has been attributed to the human colonic microbiota after in vitro studies with human fecal microbiota [ 22 ] and evaluation of microbial extracts with antiproliferative activity [ 23 ]. Phase II metabolites of hydroxybenzoic acid, such as its glucuronides, have been detected in urine after consumption of orange juice [ 24 ] and red raspberries [ 25 ], or after an organic diet [ 26 ]. 4-hydroxybenzoic acid, one of the modified but non-conjugated forms, has also been described as a derivative of pelargonidin thanks to studies with oral gavage of that particular polyphenol in animal models [ 27 ] and of cyanidin-3-glucoside after oral administration of this other polyphenol in clinical studies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in 4-hydroxibenzoic acid was observed in urine after an intervention with organic products (more than 80% of the diet coming from organic supermarkets) carried out by our group [ 26 ], as well as an increase of constituents from the hydroxybenzoic acid family after different types of (polyphenol-rich) foods such as oranges, cocoa, and almonds, or beverages like green tea, coffee, and red wine [ 6 ]. In addition, a prior study within the PREDIMED cohort showed that intake of hydroxybenzoic acid, among other (poly)phenols, was correlated with a lower incidence of type 2 diabetes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%